Learning mathematics successfully : raising self-efficacy in students, teachers and parents - Hickman, Clark J.; Sherman, Helene J. (Emerald Publishing Limited : Information Age Publishing Inc., 2019)
"This book is an important resource for pre-service and in-service teachers, as well as families in applying the theory of self-efficacy to support learners in becoming confident and assured in their ability to understand and apply mathematical principles and procedures. Coupled with classroom ready mathematics instructional strategies, the book provides readers with the background, tools and strategies needed to carry content success and confidence forward to remain persistent in solving all future mathematical problems"--